2001
DOI: 10.1097/00006231-200105000-00006
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of three different 99mTc-labelled radiopharmaceuticals for sentinel lymph node identification

Abstract: This work was designed to compare sentinel lymph node (SLN) uptake of 99mTc-labelled human serum albumin colloid (99mTc-HSAC), 99mTc-labelled antimony sulphur colloid (99mTc-SC) and a 99mTc-labelled dextran 70 solution (99mTc-Dx) and their selectivity in the identification of this node in the right rear footpad (RRF) of normal mice and tumour bearing mice. Radiopharmaceutical uptake in the SLN (popliteal lymph node) and the lumbar lymph node (LLN), the second lymphatic node station from RRF, were measured at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 10 publications
0
10
0
5
Order By: Relevance
“…In the latter, the SLN of the footpad was always the popliteal from which the radiopharmaceutical ascends to the inguinal and lumbar lymphatic basins (7).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, the SLN of the footpad was always the popliteal from which the radiopharmaceutical ascends to the inguinal and lumbar lymphatic basins (7).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid absorption and transport with a prolonged selective sequestration in the SLN allows accurate detection up to 24 h after injection. Spill to second-echelon nodes is minimal and non-disturbing [5,6,14,[21][22][23][24][25]. 99m Tc-HIG is a successful and promising new agent for visualizing the lymphatic system.…”
Section: Discussionmentioning
confidence: 99%
“…The colloid employed should be of a size to be taken up efficiently and retained within the sentinel node. It has been shown that the highest counts in recovered sentinel nodes were from 100 to 200 nm albumin colloid particles [31] . Filtered 99m Tc-sulphur colloid (100 nm filtered) has a faster transport rate to the regional nodes and lower radiation dosimetry.…”
Section: Technical Issuesmentioning
confidence: 99%